Synthesis, characterization and biological activities of organotin(IV) complexes with hydrazone/carbohydrazone ligands - Norrihan, Sam (Universiti Malaysia Sarawak (UNIMAS), 2013)
This thesis report four new chelating hydrazone, carbohydrazone ligands and their organotin(IV) complexes. The four ligands namely 2-hydroxynapthaldehyde 4-benzhydrazone [NHB, (1)], benzoylacetone 4-benzhydrazone [BAHB, (2)], ortho-vanillin hydrazone [VHP, (16)] and carbohydrazone-bis(2-acetylpyridine) [CBAP, (24)] have been synthesized. Subsequently, four series of new organotin(IV) complexes have been synthesized by direct reactions of RnSnCl4-n (R= Me, Bu, tBu, Ph; n=1, 2), base and ligands in dry methanol with 1:1:1 or 1:2:1 mole ratio under dry nitrogen atmosphere. All ligands and their organotin(IV) complexes (3-15, 17-23 & 25-28) have been characterized by elemental analyses, molar conductivity, UV-Visible, FTIR and 1H NMR spectral studies. Thirteen new organotin(IV) complexes of the ligands (1-2) of general formula [RnSnCl4-n (NHB)] [R= Me2, n= 2 (3); R= nBu2, n= 2 (4); R= Ph2, n= 2 (5); R= Me, n= 1 (6); R= nBu, n= 1 (7); R= Ph, n= 1 (8)] and [RnSnCl4-n(BAHB)] [R= Me2, n= 2 (9); R= nBu2, n= 2 (10); R= tBu2, n= 2 (11); R= Ph2, n= 2 (12); R= Me, n= 1 (13); R= nBu, n= 1 (14); R= Ph, n= 1 (15)] have been synthesized. The X-ray crystallography diffraction analyses of compounds (3-4, 9 & 12) confirmed that all are trigonal bipyramidal geometry and both ligands (1-2) acted as a dinegative tridentate nature via ONO-donor atoms. Another type of hydrazone ligand, [VHP] (16) and its organotin(IV) complexes, [R2SnCl2(VHP)] [R = Me (17), Ph (18), nBu (19) and tertBu (20)], [RSnCl2(VHP)] [R = nBu (21)and Ph (22)] and [SnCl3(VHP)] (23) were also prepared and characterized. All spectroscopic data suggested that ligand (16) acted as a neutral bidentate chelating agent in complexes (17-20) whereas ligand (16) acted as a uninegative tridentate nature in complexes (21-23).Four organotin(IV) complexes of formula [RnSnCl4-n(CBAP)], where R= Ph2, n= 2 (25); R= nBu2, n= 2 (26); R= Ph, n= 1 (27) and R= nBu, n= 1 (28) have been synthesized by direct reaction of organotin(IV) chloride(s) with carbohydrazone-bis(2-acetylpyridine) ligand [(CBAP), (24)] in the presence of KOH in 1:1:1 (ligand:base:metal) mole ratio in absolute methanol. In organotin(IV) complexes (25-26), the ligand (24) acted as a neutral bidentate chelating agent in complexes (25-26). However, the ligand (24) acted as a mononegative tridentate chelating agent in complexes (27-28). A octahedral structure has been proposed for the organotin(IV) complexes (25-28). Ligands (1-2, 16 & 24) and their organotin(IV) complexes (3-15, 17-23 & 25-28) were tested for their cytotoxicity against Artemia salina. LC50 values showed that most of the organotin(IV) complexes are more toxic compared to their free ligands (1-2 & 24). However, the [VHP] (16) ligand showed moderate activity towards Artemia salina. The diphenyltin(IV) complex showed highest toxicity compared to the other organotin(IV) complexes. All ligands (1-2 & 16) and their organotin(IV) complexes (3-15 & 17-23) were also tested against five types of bacteria namely Bacillus cereus, Staphylococcus aureus, Escherichia coli, Enterobacter aerogenes and Salmonella typhi. It was found that all the organotin(IV) complexes were more active against the bacteria tested than the free ligands but low activity compared to the doxycycline which served as positive controls (reference drug).